Geographic Mobility over the Life-Cycle - Antonia Diaz; Álvaro Já\~nez; Felix Wellschmied (Institute of Labor Economics (IZA), 2023)
When mobility between locations is frictional, a person's economic well-being is partially determined by her place of birth. Using a life cycle model of mobility, we find that search frictions are the main impairment to the mobility of young people in Spain, and these frictions are particularly strong in economically distressed locations. As a result, being born in a high-unemployment urban area carries with it a large welfare penalty. Less stable jobs, slower skill accumulation, lower average wages, and fewer possibilities for geographic mobility all contribute to these welfare losses. Paying transfers to people in distressed economic locations decreases these welfare losses without large adverse effects on mobility. In contrast, several policies that encourage people to move to low-unemployment urban areas increase these welfare losses and fail to meaningfully increase mobility towards these more successful locations.
Keywords: E20; E24; E60; J21; J61; J63; J64; J68; R23; R31; 330; mobility; local labor markets; search frictions; life cycle; dynamic spatial models